2002
DOI: 10.1186/1471-2229-2-1
|View full text |Cite
|
Sign up to set email alerts
|

The molecular genetic linkage map of the model legume Medicago truncatula: an essential tool for comparative legume genomics and the isolation of agronomically important genes

Abstract: Background: The legume Medicago truncatula has emerged as a model plant for the molecular and genetic dissection of various plant processes involved in rhizobial, mycorrhizal and pathogenic plant-microbe interactions. Aiming to develop essential tools for such genetic approaches, we have established the first genetic map of this species. Two parental homozygous lines were selected from the cultivar Jemalong and from the Algerian natural population (DZA315) on the basis of their molecular and phenotypic polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(31 citation statements)
references
References 74 publications
3
28
0
Order By: Relevance
“…Under such stressful conditions, DHNs accumulate in most tissues and cells and are mainly distributed in the nucleus and cytoplasm of the plant cell. Previous studies indicated that DHNs interact with the chloroplast (Mueller and Fernando, 2003; Tunnacliffe and Wise, 2007), mitochondria (Borovskii et al, 2002; Grelet, 2004), tonoplast (Heyen et al, 2002), endoplasmic reticulum (ER) (Ukaji et al, 2001), cytosol (Roberts et al, 1993), and nuclei (Liu et al, 2013). Some DHNs were found to accumulate in the root tip, open stomata, and cells surrounding the vascular tissue, suggesting that these proteins may play roles in these special tissues under non-stress conditions (Nylander et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Under such stressful conditions, DHNs accumulate in most tissues and cells and are mainly distributed in the nucleus and cytoplasm of the plant cell. Previous studies indicated that DHNs interact with the chloroplast (Mueller and Fernando, 2003; Tunnacliffe and Wise, 2007), mitochondria (Borovskii et al, 2002; Grelet, 2004), tonoplast (Heyen et al, 2002), endoplasmic reticulum (ER) (Ukaji et al, 2001), cytosol (Roberts et al, 1993), and nuclei (Liu et al, 2013). Some DHNs were found to accumulate in the root tip, open stomata, and cells surrounding the vascular tissue, suggesting that these proteins may play roles in these special tissues under non-stress conditions (Nylander et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The first steps towards sequencing were taken when Nam et al (1999) produced the first BAC clones from Jemalong A17. The first published genetic map of M. truncatula was produced by Thoquet et al (2002) using two homozygous lines selected from Jemalong (Jemalong 6 or J6) and the Algerian natural population DZA315. Thoquet et al (2002) noted that the three Jemalong lines A17, J5 and J6 could be considered to have an identical genotype (but different to the highly regenerable Jemalong genotype 2HA).…”
Section: Medicago Truncatula As a Model Legumementioning
confidence: 99%
“…The first published genetic map of M. truncatula was produced by Thoquet et al (2002) using two homozygous lines selected from Jemalong (Jemalong 6 or J6) and the Algerian natural population DZA315. Thoquet et al (2002) noted that the three Jemalong lines A17, J5 and J6 could be considered to have an identical genotype (but different to the highly regenerable Jemalong genotype 2HA). BAC clones were mapped to M. truncatula A17 pachytene chromosomes by fluorescent in situ hybridisation (FISH), (Kulikova et al 2001;Choi et al 2004a;Kulikova et al 2004).…”
Section: Medicago Truncatula As a Model Legumementioning
confidence: 99%
See 1 more Smart Citation
“…Medicago truncatula (Medicago) is a well-established model for studying legume biology and, in particular, the molecular mechanisms mediating symbiotic associations (Cook, 1999). The Medicago research community has developed many genetic, proteomic, and genomic tools, including the recent release of its genome sequence (Thoquet et al, 2002; Ané et al, 2008; Colditz and Braun, 2010; Young et al, 2011). …”
Section: Introductionmentioning
confidence: 99%